Analysis of the Role of Livestock Sub-Sector in Economic Growth in West Sumatra. Issue 1 (March 2021) - Suresti, A; Tan, F; Adrimas,; Dinata, U
Abstract: This study aimed to analyze the role and growth of the livestock on economic development in West Sumatra Province. This study used Analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Shift Share Analysis. The data used in this study had secondary data from the 2016-2019 period. The research method used Desk Study. The results showed that the livestock was a non-basis sub-sector. The average LQ value of in 2016-2019 was 0.96 and And this sub sector will remain a non-base in the future, this showed that the livestock had not changed its role in the future. The determining factor for this change in role was the structure of the economy.